Between lecture and flipped: The use of "labs" in the public administration classroom. Issue 3 (October 2019) - Engbers, Trent
The use of applied labs has long been an established practice in the natural sciences as a means of stressing application of theoretical principles and fostering disciplinary excitement. The social sciences have seen an advent of similar problem-based approaches, but have not adopted a lab-based model. Labs offer an opportunity to use class time for purposes of application without moving fully to a flipped classroom model. This article presents the use of labs in three undergraduate public administration classes: Introduction to Public Administration, Research Design and Data Collection, and Statistics and Data Analysis. The labs are collaborative and feature both peer and instructor support. They utilized an established problem-based strategy to demonstrate the real-life applicability of academic topics (Kolb, 1984 ;Kramer and Schechter, 2011 ). Data collected from 10 sections of the courses before and after implementation show increased student satisfaction and greater self-reported learning, though the effect on academic performance is more moderated.